Teacher creativity in early grade reading learning process in online system in the ERA of COVID-19 pandemic: Analysis based on total quality management theory of education - Hartanti, Christina Dwi; Haryono, Frans; Sungkowo, Edy; Rusdarty, Rusdarty (Edelweiss Applied Science and Technology, 2025)
The spread of Covid-19 has changed human life, including the world of education, especially in the learning process. The learning process, which originally used an offline system, was changed to an online system. These two systems have different fundamental differences. Therefore, it requires teacher creativity related to reading lessons in the online system, so that the learning process takes place effectively, efficiently, and safely. This study discusses teacher creativity in the learning process in three elementary schools in the early grades in the Special Region of Yogyakarta, namely Mutiara Persada International Elementary School, SDN Nogopuro, and SDN 1 Suryodiningratan. Through qualitative research and Edward Sallis’ Total Quality Management of Education (TQME), the results of this study show that the most important aspect in the learning process during the Covid-19 pandemic is the teacher’s more humane attitude towards students. This attitude is part of creativity, in addition to other forms of creativity that are technical in nature. In the context of learning, Covid-19 can be "defeated" by the human attitude itself.